Effect of deicing agents on the performance of airport asphalt pavement - Li, Ping; Peng, Wenju; Han, Yanlong; Wang, Bin; Liu, Zhaohui; Li, Wei; Wei, Wanfeng (Frontiers in Materials, 2023)
Deicing agents are widely used to remove ice and snow on airport pavement, ensuring air traffic operation and safety. However, excessive spraying may affect the performance of airport pavement. The effects of different chloride deicing agents on the performance of airport asphalt and mixture have been assessed by previous studies. The three deicing agents (NaCl, KHF-1A, and NW056) were selected. Conducting various tests to examine their influence on the performance of asphalt and asphalt mixture. The tests include the DSR test, BBR test, indirect tensile test, bending test of small beam, and freeze-thaw splitting test. The results indicate that the asphalt anti-rutting factor G * / sinδ varies by 25% -45%, the asphalt creep stiffness increases by 15% -50%, and the anti-fatigue factor (G * sinδ )increases by 10% -40% under the effect of the deicing agents. The splitting strength of the mixture decreases by 10% -40%, the bending stiffness modulus increases by 6% -20%, and the freeze-thaw splitting strength ratio does not change significantly under the effect of the deicing agents. NW056 deicing agent has minimal effect on the performance of airport pavement and has optimal performance. The replacement of traditional chloride deicing agents helps to prolong the service life of airport asphalt pavement.